\(\displaystyle \L -\frac{3}{4x} \,=\, -9\)

Perform the following operation on both sides: multiply by -1.

\(\displaystyle \L \left(-\frac{3}{4x}\right) \times \,\left(-1\right)\, =\, -9 \, \times \, -1\)

Result: \(\displaystyle \L \,\frac{3}{4x}\, =\, 9\)

Perform the following operation on both sides: multiply by 4x.

\(\displaystyle \L \left(\frac{3}{4x}\right)\, \times \, \left(4x\right) \,=\, 9 \, \times \, \left(4x\right)\)

Result: \(\displaystyle \L \,3 \,=\, 36x\)

Perform the following operation on both sides: divide by 36.

\(\displaystyle \L 3\, \div \,36 \,=\, 36x\, \div \,36\)

Result: \(\displaystyle \L \,x\, =\, \frac{3}{36}\, =\, \frac{1}{12}\\)

As you progress further in equation solving, you'll see that some operations are not allowed, like dividing by 0.